Assessing Smart Service Adoption in South African Townships: An Extended UTAUT Framework - Nojila, Olebogeng Hellen; Chukwuere, Joshua; Gorejena, Karikoga (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
The concept of smart cities has emerged globally in response to rapid urban migration. However, in South Africa, many citizens still live on the peripheries of urban centers due to spatial and socio-economic inequalities stemming from apartheid, which displaced and marginalized township and rural populations. This study explores the factors influencing the adoption and acceptance of smart services in South African townships and assesses the moderating effects of the Unified Theory of Acceptance and Use of Technology (UTAUT) variables. To enhance the UTAUT framework, the study incorporates trust, self-efficacy, and perceived risk as additional constructs. A random survey was distributed to township residents, with a targeted sample size of 384. A total of 472 valid responses were analyzed. The findings reveal that social influence, trust, perceived risk, income, and education significantly determine smart service adoption. Furthermore, age, gender, income, and education were found to moderate user behavior, impacting both acceptance and practical use of these services. The results offer valuable insights for policymakers and service providers in townships, highlighting the importance of understanding the roles of social influence, trust, security, income, and education. These insights can guide the development of inclusive smart services, tailored awareness campaigns, secure technologies, and targeted digital skills programs, ensuring that smart service initiatives are equitable and effective in township contexts.